(untitled) (Revista Nacional de Odontología, 2021)
Odontogenic infections (OI) are related to dental pulp and periodontal involvement, they are polymicrobial but strict anaerobes predominate. In addition to drainage or surgical management, antimicrobials are used that shorten the resolution time and favor outcome, predominantly in terms of probing depth (PD) reduction and attachment-level gain. The most commonly used antimicrobials are beta-lactams combined with betlalactamase inhibitor, nitroimidazole metronidazole, azithromycin among macrolides, lincosamine mainly clindamycin and quinolone with greater success with moxifloxacin. Different regimens of these antimicrobials have been used to determine noninferiority in the majority, but specific advantages have been found with the use of some as the shortest time of therapy, the greatest effectiveness in the case of the emergence of bacterial resistance and fewer side effects.